Cognitive task effects on blood flow velocity changes in middle cerebral arteries: A transcranial Doppler study of hemispheric specialization - Tadinac Babić, Meri (Array, 1993)
The aim of this study was to determine whether there are differences between the left (LH) and right (RH) hemisphere in the blood flow velocity changes in the middle cerebral arteries (MCA) during the performance of verbal and visuo-spatial tasks. Thirty-four female subjects, fulfilling all the necessary criteria for laterality studies, participated in the experiment. The blood flow velocity in the right and left MCA was measured unilaterally by means of a transcranial Doppler device (TCD) during the performance on two verbal and two nonverbal tasks. The comparison of blood flow velocity increase in left and right MCA showed a tendency of larger increase in the LH for verbal tasks and ih the RH for visuospatial tasks, but only one difference, that of the semantic association task, reached statistical significance. The results are discussed in terms of the current findings in laterality research.